An exploratory study of the histomorphogenesis and zonal vascular changes in the human fetal medial meniscus - Sushma Prabhath; Kurian Alappatt; Ashwija Shetty; Suhani Sumalatha (Elsevier, 2021)
Background: Menisci plays an essential role in the functioning of the knee joint. It is mainly composed of water, collagen, and glycosaminoglycans. The cells seen in the menisci are fibrochondrocytes, mostly confined to the middle and inner zone of menisci. The morphogenesis of the developing menisci is not clearly understood. The present study intended to evaluate the morphological changes in the developing menisci by assessing the changes in the distribution of cells, fibers, and the extent of blood vessels within the medial menisci of fetuses of different developmental weeks. Method: ology: The present cross-sectional study was carried out on 48 fetuses divided into eight groups based on the week of development. The right knee was uniformly selected to procure the medial menisci which were further processed for microscopic observations. The cell density in the menisci was quantified at a fixed site in all the documented images. The arrangement of the blood vessels and collagen fibers was also observed. Results: Cell quantification showed that the menisci were highly populated with cells in the early stages of development which gradually decreased on development. The collagen fibers were orderly arranged in the later stages of development. The early menisci were entirely penetrated with blood vessels which were noted only in the periphery by the 29th week of gestation. Conclusion: Histomorphogenesis of the medial menisci is important to surgeons, orthopedicians, and other interventionists while planning arthroscopic procedures and other advanced orthopedic surgeries. The present study helps us understand the morphological changes in the medial menisci at different developmental stages. Further, the study may also serve as a database to record the changes occurring in the number and arrangement of the cells, fibers, and vascularity in the developing medial menisci.